Los planes de vida y la política indígena en la Amazonía peruana - Espinosa, Oscar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
In this article the political dimension of the «planes de vida indígena» (indigenous life plans) are discussed in three cases from the Peruvian Amazon region. In these cases, the «planes de vida» have fulfilled a role in the process of indigenous self-government or in the negotiation of the indigenous agenda vis-à-vis the State. The three cases studied are those of the Achuar people, an Ashaninka local organization – the Central Asháninka del Río Ene (CARE) – and the case of AIDESEP, the national-level indigenous organization for the Amazon region in Peru.

Este artículo busca discutir la dimensión política de los planes de vida indígena, tomando en consideración algunos casos de la región amazónica peruana. En concreto, se discuten tres casos específicos en que los planes de vida indígena han sido utilizados como un instrumento de autogobierno o de negociación política entre las sociedades indígenas y el Estado peruano: el del pueblo achuar, el de la Central Asháninka del Río Ene (CARE) y el de la Asociación Interétnica de Desarrollo de la Selva Peruana (AIDESEP).
Life plans and indigenous politics in the Peruvian Amazon
Keywords: Amazonía; Política indígena; Plan de vida; Planificación; Desarrollo; Asháninka; Achuar; Organizaciones indígenas; Perú; https://purl.org/pe-repo/ocde/ford#5.04.03